Mitigating the Risk of Radicalization: Management Strategies for Religious Moderation Programs in Islamic Boarding Schools - Faidkholidi, Faidkholidi; Fajri, Zaenol (Journal of Educational Management Research, 2025)
This study aims to explore the implementation of religious moderation values as a preventive measure against radicalism in Islamic elementary education. The research adopts a qualitative case study approach. Data were collected through observation, in-depth interviews, and documents. The Findings show that key values such as tasamuh (tolerance), tawassuth (moderation), i’tidal (balance), and muwathanah (civic responsibility) are systematically embedded in formal learning, religious practices, and school culture. Teachers and principals play vital roles as role models and facilitators who promote inclusive dialogue and critical thinking. Contextual teaching methods—such as open discussion, case studies, and reflective practice—help students internalize these values beyond theoretical understanding. Extracurricular activities further support character formation by encouraging cooperation, leadership, and respect for diversity. However, implementation is challenged by the absence of specific instructional materials, limited teacher training in diversity education, and the influence of unregulated digital content that may expose students to radical narratives. This study highlights the importance of incorporating religious moderation into Islamic elementary education as a means to counter radicalization. The findings suggest that educational institutions should prioritize teacher training, develop specific teaching materials, and enhance digital literacy to safeguard students from radical influences.